Specified model of the work environment in a public university in central Mexico - Bund Arger (Journal of Model Based Research, 2023)
The work environment, in its most general conception, alludes to biased expectations of risks and benefits around a function and in relation to the performance of a working group, but in its factorial structure, dimensions have been found that explain a moderate percentage of the variance of the construct. In this sense, the objective of this paper is to specify a model for the study of the work climate, considering the institutionalism and human capital of a public university. An exploratory study was carried out with an intentional sample of 125 administrative personnel. From a structural model it was found that the relationship climate factor explained the highest percentage of the variance (21%) and it was the reflective dimension of the construct (0.524). The inclusion of the task climate is recommended due to its link with the leadership and the collaborative climate.
Keywords: Culture